(untitled) (Journal of Asian Development Studies, 2023)
Emotional intelligence in the classroom is a crucial area of research in many academic disciplines regarding secondary students’ academic achievement and self-worth in the Dera Ismail Khan district of Pakistan. The study’s main objective was to assess CEI’s impact on students’ SE. The second objective was to ascertain the effects of emotional intelligence in the classroom on the academic performance of secondary school students. A total of 20 secondary schools were selected from both rural and urban areas of Dera Ismail Khan. The population consisted of 49000 secondary school students. The sample of study 490 was comprised of 276 science students and 215 art students. Two questionnaires were constructed, i.e., the classroom emotional intelligence questionnaire (CEIQ) and the self-esteem questionnaire (SEQ). Fifteen educational experts validated all items of both CEIQ and SEQ. Still, the reliability of the data was assessed using the Cronbach alpha test. The dependability of the EI was 0.811, and the SE was 0.801. The findings of the study reveal that there is a positive relationship between classroom emotional intelligence with self-esteem (r=.06**) and the academic achievement of students (r=.58**). The study recommended that students be given more resources and encouragement to express their destructive emotions before they label them with any undesirable characteristics.